Surgical Outcomes of Intussusception with Intestinal Perforation in the Pediatric Population: A Six-Year Prospective Study - Mumtaz Ahmed Qureshi, Imtiaz Ahmed Qureshi, Roshan Ali Siyal, Iqra Aslam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Intussusception is a leading cause of intestinal obstruction in children. While most cases respond to non-operative reduction, perforation remains a rare but devastating complication with high morbidity and mortality. Prospective data on disease-related perforated intussusception from resource-limited settings are scarce. Objective: To evaluate surgical outcomes, complications, and prognostic factors in children with perforated intussusception. Methods: A prospective study was conducted at the Department of Pediatric Surgery, Liaquat University Hospital, Hyderabad, Pakistan (December 2015–December 2021). Children aged 2 months to 12 years with confirmed intussusception and intestinal perforation requiring surgery were enrolled. Logistic regression identified independent mortality predictors. Results: Forty-two children (mean age 18.6±14.2 months; 64.3% male) were included. Mean symptom duration was 4.2±1.8 days, with 66.7% presenting beyond 72 hours. Bowel resection with primary anastomosis was performed in 78.6%; pathological lead points were identified in 38.1%. Postoperative complications occurred in 61.9%, including surgical site infection (35.7%), sepsis (21.4%), and anastomotic leak (14.3%). Mean hospital stay was 14.8±6.4 days. Mortality was 11.9%. Independent mortality predictors included delayed presentation >72 hours (OR 4.8; p=0.025), septic shock on admission (OR 12.6; p=0.001), bowel necrosis >30 cm (OR 8.4; p=0.005), and anastomotic leak (OR 7.2; p=0.018). Conclusion: Perforated intussusception carries substantial morbidity and mortality. Delayed presentation is the most critical modifiable risk factor; early recognition and prompt intervention are essential. Keywords: Intussusception, intestinal perforation, pediatric surgery, surgical outcomes, bowel resection.